Recent Advances in Plant Biotechnology - Kirakosyan, Ara. (Springer US, 2009)
For this volume, we have brought together a group of contributors who address the most recent advances in plant biotechnology and what they mean for human progress and a more sustainable future. Plant biotechnology, which is gaining in importance, applies in three major areas: the control of plant growth and development, the protection of plants against environmental and biotic stresses, and the expansion of ways by which specialty foods, biochemicals and pharmaceuticals are produced. Our lives are being affected in many ways, particularly in connection with sustainable food production and distribution systems, genetically modified organisms, integrative medicine strategies to treat human diseases, bioremediation of toxic waste sites, alternative energy production systems that utilize bioenergy sources, and both risks and benefits that fall within the rubric of plant biotechnology. The topics covered in Recent Advances in Plant Biotechnology will be a valuable resource to plant biotechnologists, plant biologists, biochemists, molecular biologists, pharmacologists, and pharmacists; agronomists, plant breeders, and geneticists; ethnobotanists, ecologists, and conservationists; medical practitioners and nutritionists; research investigators in industry, federal laboratories, and universities; and students and teachers in the biological and biomedical sciences. Instructors and students will find particular interest in the provided content on plant functional genomics, gene and metabolic engineering, and molecular farming, as well as in the multiple examples of the transition from fundamental science to technological applications.